(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
The distribution of state subsidies to non-governmental non-profit organizations is not only a financial procedure, but also an institutional process that affects public trust, civic participation and the effectiveness of social policy. In modern public administration, this process should be based on digital governance, openness and clear institutional responsibility.